2018
DOI: 10.3390/beverages4030060
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Properties and Heavy Metal Contents of Commonly Consumed Alcoholic Beverages Flavouredwith Herbal Extract in Nigeria

Abstract: Abstract:There is proliferation of alcoholic beverages flavoured with herbal-extracts that are perceived to have medicinal values. Information on the phytochemical and heavy metal contents of these products is scarce. This study assessed the phytochemical properties and heavy metal contents of herbal-extract flavoured alcoholic beverages in major motor parks in Ibadan, Nigeria. The phytochemical properties of the beverages were determined in triplicate using standard methods, while the heavy metal contents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…The concentration of Fe was within the MPL limit of 0.30mg/l (WHO, 2017), which was lower than that reported by Van-Wyk et al, [59] (19.167-632.361 µg/l) and Okareh et al [65] (720-4220 µg/l). Fe can come via water/process container leaching, and in high enough concentrations, it can give the beverage an unpleasant taste.…”
Section: Heavy Metals Concentration In the Alcoholic Beveragescontrasting
confidence: 52%
“…The concentration of Fe was within the MPL limit of 0.30mg/l (WHO, 2017), which was lower than that reported by Van-Wyk et al, [59] (19.167-632.361 µg/l) and Okareh et al [65] (720-4220 µg/l). Fe can come via water/process container leaching, and in high enough concentrations, it can give the beverage an unpleasant taste.…”
Section: Heavy Metals Concentration In the Alcoholic Beveragescontrasting
confidence: 52%
“…[20]. While Pb and Cr were lower than those reported [8] in Phytochemical properties and heavy metal contents of commonly consumed alcoholic beverages flavoured with herbal extract in Nigeria. The level of Co obtained in this study is consistent with the result reported [8] while Zn and Fe concentrations were higher.…”
Section: Comparison Of the Total Elemental Concentrations With Similar Studiesmentioning
confidence: 98%
“…In parallel with the increasing interest in the therapeutic benefits of herbal products, there has been an increasing concern over the safety and toxicity of natural herbs and formulations available on the market. There is a widespread misconception that natural herbs and plants are inherently safe; nevertheless, there has been a large volume of reports on incidences of toxicity and adverse effects linked to the use of herbal plants and their formulations in different parts of the world [7,8]. In Nigeria, the herbal concoctions are formulated by soaking the herbal plants in either water or alcohol so as to obtain the plant extracts.…”
Section: Introductionmentioning
confidence: 99%